INTERDEPENDENCE DAN CONTAGION EFFECT TERHADAP PASAR MODAL DI KAWASAN REGIONAL ASEAN - GUNARDI, PRASTIONO (Universitas Katolik Widya Mandala Surabaya, 2012)
This study aims to determine the relationship of each countries around the ASEAN region (Malaysia, Thailand, Philippines, Singapore, and Indonesia). Also it wants to know the direction of the relationship interdependence and Contagion that could form the direction of the crisis in ASEAN from Singapore, Malaysia, Indonesia to Philippines. The analysis used in this study is the analysis of the correlation coefficient matrix of the index return in the ASEAN region and using the Granger Causality analysis based on the index return in the ASEAN region secondary data during period 2008 to 2011. The results of this study found that the capital markets in ASEAN countries except Thailand which is integrated with each other and there is interdependence relationship in ASEAN capital markets so as to make Turbulence.